Personality traits and the likelihood of self-employment: A journey into the crafts' way of doing business - Petrik Runst; Jörg Thomä (German Economic Review (GER), 2025)
Given the renewed scholarly interest in the crafts, this paper explores the nuances of crafts entrepreneurship through a personality-based approach. Our findings validate prior research on the general influence of broad and narrow personality traits on self-employment. However, our analysis also suggests that certain effects differ between crafts and non-crafts, most notably the role of the Big Five trait of conscientiousness - suggesting that there is something 'unique' about the crafts' way of doing business that goes beyond firm size. In this way, we provide evidence that personality may affect self-employment differently depending on the sector or field of entrepreneurship.
Keywords: L26; M13; D91; 330; crafts sector; entrepreneurship; personality traits; self-employment